The price of media capture and the looting of newspapers in interwar France - Vincent Bignon; Marc Flandreau (Graduate Institute of International and Development Studies, 2012)
This paper develops a new insight enabling the empirical study of media capture: minority shareholders of newspapers and readers face similar risks. Both are adversely affected when corrupt insiders use the newspaper for personal profit and receive invisible revenues. This means that relevant data on influence and exploitation of newspaper has been hiding in plain sight in stock exchange or over-the-counter prices, since stock transactions reflect the value of this capture. Empirical data is consistent with increasing levels of looting in France during the 1930s. We provide a comparison with Britain and argue that Britain managed to protect its newspapers better.
Keywords: D72; G34; L82; N24; N74; 330; media; governance; minority shareholders; control premium; corruption; interwar; France; Mediensektor; Corporate Governance; Eigentümerstruktur; Korruption; Geschichte; Frankreich; Großbritannien